A new species of leaf porter crab of the genus Neodorippe Serène & Romimohtarto, 1969 (Crustacea, Decapoda, Brachyura, Dorippidae) from Irian Jaya, Indonesia - Ng, P.K.L. (2014)
Proceedings of the Biological Society of Washington